Reviewer Acknowledgements - Williams, Richard (Journal of Agricultural Studies, 2021)
Journal of Agricultural Studies (JAS) would like to acknowledge the following reviewers for their assistance with peer review of manuscripts for this issue. Many authors, regardless of whether JAS publishes their work, appreciate the helpful feedback provided by the reviewers. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Each of the reviewers listed below returned at least one review for this issue. Reviewers for Volume 9, Number 2 Ai-Ping Wu, Hunan Agricultural University, China Alessandra M. Lima Naoe, Federal University of Tocantins, Brazil Alexandra-Nadia Cirdei, Technical University of Civil Engineering of Bucharest, Romania Alexandru Ioan Apahidean, Univ. of Agricultural Sciences and Veterinary Medicine, Romania Ana Daniela Lopes, Universidade Paranaense, Brazil Anca-Luiza Stanila, ICPA, Romania André Luiz Rodrigues Magalhães, UFAPE, Brazil Angel Ramon Sanchez Delgado, Universidade federal Rural do Rio de Janeiro, Brazil Arnaud Z. Dragicevic, IRSTEA, France Cleber Duarte, University of Guararapes, Brazil Darwin Pangaribuan, University of Lampung, Indonesia Eben von Well, Agricultural Research Council, South Africa Eliana Mariela Werbin, National University of Cordoba, Argentinian Eric Krawczyk, University of Michigan, USA Eric Owusu Danquah, CSIR-Crops Research Institute, Ghana Ernest Baafi, CSIR-Crops Research Institute, Ghana Ewa Moliszewska, Opole University, Poland Fernando Coelho Eugenio, Federal University of Santa Maria, Brazil Fernando Rodrigues de Amorim, State University of Paulista (UNESP), Brazil Habu Saleh Hamisu, National Horticultural Research Institute, Nigeria Hedayatollah K. Soureshjani, Ferdowsi University of Mashhad, Iran João Manoel da Silva, Universidade Federal de Alagoas, Brazil Jorge A. López, University Tiradentes, Brazil Juliana Nneka Ikpe, Akanu Ibiam Federal Polytechnic, Nigeria Mahyar Gerami, Sana Institute of Higher Education, Iran Mariana Esteves, Luiz de Queiroz College of Agriculture University of Sao Paulo, Brazil Mohammed El Basuini, Kagoshima University, Japan Mpho Tshikororo, University of Venda, South Africa Nkemkanma Vivian Agi, Rivers State University Port Harcourt, Nigeria Radu Liviu Sumalan, University of Agricultural Sciences and Veterinary, Romania Raul Pașcalău, Banat’s University, Romania Saiful Irwan Zubairi, Universiti Kebangsaan Malaysia (UKM), Malaysia Sait Engindeniz, Ege University Faculty of Agriculture, Turkey Samir Neggaz, Université Oran, Algeria Servet Aras, Bozok University, Turkey Shubha Kumari, ICAR-RCER, India Sina Nabaei, Azad University, Iran Sybelle Mesquita Silva, Universidade Federal de Alagoas, Brazil Toncho Gospodinov Penev, Trakia University, Bulgaria Tugay Ayasan, Osmaniye Korkut Ata University, Turkey Utkarsh R. Moon, Mahatma Gandhi College of Science, India Wossenie Shibabaw Mebratie, Bahir Dar University, Ethiopia Zakaria Fouad Abdallah, National Research Centre, Egypt Richard Williams Editorial Assistant Journal of Agricultural Studies ————————————– Macrothink Institute 5348 Vegas Dr.#825 Las Vegas, Nevada 89108 United States Phone: 1-702-953-1852 ext.521 Fax: 1-702-420-2900 Email 1: jas@macrothink.org Email 2: jas@macrothink.com URL: http://jas.macrothink.org